2011
DOI: 10.1177/0731684411411337
|View full text |Cite
|
Sign up to set email alerts
|

Stress-relaxation behavior of lignocellulosic high-density polyethylene composites

Abstract: In this study, stress-relaxation performance of HDPE-based injection-molded composites containing four types of natural fibers (i.e., wood flour, rice hulls, newsprint, and kenaf fiber) at 25 and 50 wt% contents, and the effect of prescribed strain levels were investigated. The results indicated that incorporating more filler causes lower relaxation values and rates, and stress retention and prescribed strain level were reversely correlated. Among the studied filler types, wood flour and kenaf fiber presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…Geethamma et al found that short coir fibers reduced the stress relaxation rate of rubber and this was attributed to fibers constraining the polymeric chains thereby preventing relaxation [ 16 ]. Mirzaei et al investigated the effect of adding various types of natural fibers in high-density polyethylene and drew similar conclusions [ 17 ].…”
Section: Introductionmentioning
confidence: 86%
“…Geethamma et al found that short coir fibers reduced the stress relaxation rate of rubber and this was attributed to fibers constraining the polymeric chains thereby preventing relaxation [ 16 ]. Mirzaei et al investigated the effect of adding various types of natural fibers in high-density polyethylene and drew similar conclusions [ 17 ].…”
Section: Introductionmentioning
confidence: 86%
“…Factors such as time and temperature have a significant effect on the viscoelastic properties of the polymeric matrix which determines the mechanical behavior of composites (Rowel et al, 2001;Nwosu-Obieogu et al, 2016). Creep analysis of composites is very essential in the study of its deformation rate prior to application, it determines the ability of the composite to withstand highest possible operating load at elevated temperature, resistance to high temperature corrosion and avoidance of material failure, these findings have ensured the reliability and durability of composites in buildings and bridge construction (Mirzaei et al, 2011;Monticelli et al, 2019;Qi et al, 2018;Sreekala et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these additional bonds, the stress relaxation rates are expected to be slower. George et al [ 6 ], and later Geethamma et al [ 7 ] and Mirzaei et al [ 8 ], have all suggested this mechanism.…”
Section: Introductionmentioning
confidence: 99%